PELATIHAN PENGGUNAAN ARDUINO UNO DAN SENSOR UNTUK MENDUKUNG PROFIL PELAJAR PANCASILA DI SMK HARAPAN MEKAR 1 MEDAN - Muhammad Furqon Siregar; Aripin Rambe; Chairul Imam (Yayasan Nusantara Hasana Berdikari, 2026)
This activity is very important to provide additional skills to SMK Harapan Mekar 1 Medan, especially in terms of social communities, flood disasters, and automatic irrigation systems. This Community Service (PkM) activity aims to improve technological understanding for teachers and students of SMK Harapan Mekar 1 Medan through training in the use of Arduino Uno and sensors. The background of this activity is the lack of additional skills programs that support technology-based learning and relevant innovation. The method used is Participatory Action Research (PAR) with a Project-Based Learning (PjBL) approach, which actively involves participants in designing and implementing sensor-based projects. The results of this activity show a clear increase in participant competency, with an average post-test score (84.57) higher than the pre-test (67.50). The training evaluation shows that 75% of participants successfully completed the final project that combines Arduino Uno and ultrasonic sensors and automatic alarm sensors into a prototype automation system. In addition, 75% of participants also successfully completed a simple project prototype, such as an automatic alarm system. This activity shows that the use of Arduino Uno and sensors can be an effective tool in developing critical and creative thinking skills, while supporting the Pancasila Student Profile.